Analysis of Visual, Auditory, and Kinesthetic Learning Styles of MTs Students in Science Learning - Sholihah, Nailatus; Wijayanti, Erna (Journal of Educational Management and Strategy, 2025)
Science learning is an intentionally designed process to facilitate students in understanding scientific concepts and developing critical thinking skills. However, based on preliminary observations at MTs Nahjatus Sholihin, it was found that students have not yet identified their individual learning styles. Consequently, they have been unable to maximize their learning potential, which affects their understanding of science subjects. This study aims to analyze the Visual, Auditory, and Kinesthetic (VAK) learning styles of eighth-grade students in science learning at MTs Nahjatus Sholihin, Rembang Regency. The research employs a quantitative descriptive method involving all 86 eighth-grade students as respondents using a total sampling technique. Data were collected through observations, questionnaires, and documentation. The results show that in all three classes, the kinesthetic learning style dominates, with percentages of 45% in class VIIIA, 40% in class VIIIB, and 41% in class VIIIC. Meanwhile, the visual learning style shows the lowest percentage, namely 22% in class VIIIA, 29% in class VIIIB, and 28% in class VIIIC. These findings indicate that most students prefer hands-on activities and learning experiences that involve movement and practice. Therefore, teachers are encouraged to apply kinesthetic-based learning strategies, such as experiments and interactive demonstrations, to optimize student engagement and achievement in science learning. This research provides important implications for science educators in designing learning activities that align with students’ dominant learning styles and contributes globally to the understanding of how culturally responsive and student-centered science instruction can enhance learning outcomes across diverse educational contexts.